Potential for opportunity recognition along the stages of entrepreneurship - Kishinchand Wasdani; Mary Mathew (Journal of Global Entrepreneurship Research, 2014)
The study primarily verifies whether ORP differs in stages of entrepreneurship and aims at identifying factors that influence ORP in different stages of entrepreneurship. The stages of entrepreneurship include pre-stage (individuals planning to start ventures), early-stage (entrepreneurs with ventures less than 3 years old) and late-stage (entrepreneurs with ventures more than 3 years in existence). The factors that were studied include personal factors (cognitive style, self-efficacy and motivation) and interpersonal factors (bridging social capital and bonding social capital). The results indicate the influence of different factors in different stages of entrepreneurship.
Keywords: 650; Entrepreneurship; Social capital; Self-efficacy; Cognitive style and Motivation